Efficiency, Fairness, and Capability Perspectives in First Aid Policy - Aga Kurniawan; Zainal Arifin Hoesein (JURNAL ILMU SYARIAH, 2025)
The recruitment policy of the State Civil Apparatus (ASN) through the Government Employees with Work Agreements (P3K) scheme is a strategic step by the Indonesian government to meet the need for professional personnel in the public sector without increasing the long-term fiscal burden. This article analyzes the P3K policy from the perspective of economic efficiency, social justice, and human capabilities, as well as the pressure of the need for inclusive and sustainable reform. The research uses qualitative methods with a normative approach and public policy analysis. Data were collected through document studies (legislation, technical guidelines, budget and performance reports), analysis of conclusions and academic papers related to ASN, and semi-structured interviews with regional/central personnel management officials, representatives of professional organizations/trade unions, as well as P3K and non-P3K ASN. The analysis was conducted using content and thematic analysis, supported by source triangulation to increase the validity of the findings. The results indicate that the implementation of P3K has the potential to increase efficiency through procurement infrastructure, optimization of human resource allocation, and fiscal discipline, but presents challenges related to equity and capabilities—particularly in aspects of career security, social protection, access to promotion and competency development, and disparities between regions and sectors. The findings also highlight the risks of dual employment status, which can impact motivation, retention, and organizational cohesion. The article recommends integrating the principles of efficiency, fairness, and capability building through: minimum protection standards and contract certainty, merit-based career paths for first responders, harmonization of remuneration and benefits, social security portability, recruitment transparency, and a monitoring and evaluation system based on performance and equality indicators. This approach is expected to encourage a more inclusive, responsive, and sustainable transformation of the Indonesian bureaucracy. Keywords: P3K, Civil Servants; Efficiency; Justice; Capability; Public Policy